ANALISIS TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Kasus pada Pemerintah Kabupaten Pasaman Barat) - Sri Adella Fitri (Tamwil, 2017)
In determining the opinion given by BPK, Kabupaten Pasaman Barat obtained an increase in opinion from 2007 to 2011. In determining the opinion given by the CPC in 2007 obtained disclaimer opinion, 2008 disclaimer opinion, 2009 obtained disclaimer opinion, 2010 obtained WDP opinion, and on in 2011 obtained a WDP opinion. Whether by gaining this opinion, the government's financial statements have reflected the report with really good disclosures and whether with the opinion of the West Pasaman district government could change it to be even better or even mediocre. This research is a research using field research research or field research using case study research method at Pasaman Barat Regency Government. The type of research is descriptive analysis because in this research will do an analysis on the level of disclosure of Local Government Financial Report based on the Financial Report of Pasaman Barat Regency Government. The average information disclosure presented in the Local Government Financial Statements per year is quite good, the account details are also quite good, but there are no further standards and rules regarding the breadth of information and account details that should be disclosed in local government financial statements.